Barriers of last mile supply chain management and reproductive, maternal, new born, and child health product availability in Ethiopia - Welelaw Necho Mulatu; Danielson K. Onyango; Happiness Mberesero; Gizachew Tadelle; Dessalew Emaway; Bezawit Mesfin; Tsegaye Shewangizaw; Chala Tesfaye; Andualem Ababu; Biruk Bogale; Kerubo Mogesi (PLoS ONE, 2026)
Background Despite notable advancements in Ethiopia’s health supply chain, critical bottlenecks persist at the last mile, particularly within health centres and health posts. This study aimed to identify barriers affecting the availability of reproductive, maternal, new-born, and child health commodities and to explore barriers, and constraints that hinder effective data use for supply chain decision-making. Methods This qualitative study employed key informant interviews with 23 participants, including logisticians, pharmacists, store managers, health extension workers, and health program experts. Data were analysed using Braun and Clarke’s thematic analysis framework. Results Six key bottlenecks emerged: [1] inconsistent delivery systems; [2] poor data quality and limited use of Logistic Management Information System (LMIS); [3] inadequate inventory management; [4] weak quantification system; [5] staffing shortages; and [6] infrastructure barriers. In pastoral areas, poor road access, limited cold storage, and low eLMIS coverage hinder direct deliveries. Agrarian regions benefit from more direct delivery coverage, but they still face challenges, including aging vehicles and poor rural roads. Across both settings, health posts, the lowest level health facility, often experience inconsistent supply and resort to self-product collection. Indirect delivery via an added layer of woreda (district) offices poses delivery delays. Broader infrastructure issues, such as inadequate storage space, unreliable power, and weak internet connectivity, compound these problems. Data management system weaknesses, including poor reporting quality, limited interoperability, and minimal data use for decision-making, persist in both contexts. Human resource constraints such as shortages of skilled personnel, high turnover, and limited training further undermine supply chain performance. Conclusions This assessment highlights interrelated bottlenecks affecting last-mile RMNCH product availability in both pastoral and agrarian areas of Ethiopia, though the severity and context-specific barriers vary. Addressing these issues requires coordinated, system-wide strategies that are tailored to regions with a focus on transportation, strengthening infrastructure, data systems, and workforce capacity.